Criterion Validity of the Minnesota Multiphasic Personality Inventory-3 (MMPI-3) at the National Level - Emami Doost, Seyed Mojtaba; Ahi, Qasem; Kamkari, Kambiz; Mansouri, Ahmad; Shahabi Zadeh, Fatemeh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to evaluate the criterion validity of the third edition of the Minnesota Multiphasic Personality Inventory (MMPI-3) at the national level.Methods and Materials: This study employed a psychometric design and was categorized under methodological research designs. The statistical population consisted of all Iranian men and women aged 18 to 50 years. From this population, 2,500 individuals were selected using proportional stratified sampling from six provinces across five geographical regions: North, South, East, West, and Central Iran. Data were collected using the Minnesota Multiphasic Personality Inventory-3 (MMPI-3) and the Millon Clinical Multiaxial Inventory-IV (MCMI-IV). The statistical model used for determining criterion validity was correlation analysis. Data analysis was conducted using SPSS version 22.Findings: The results indicated that there were significant correlations between the clinical scales of the MMPI-3 and the MCMI-IV using the correlation method.Conclusion: Based on the findings of the study, the MMPI-3 demonstrates validity in assessing clinical scales and is considered a valid instrument. Therefore, it can be utilized for evaluating the clinical characteristics of Iranian citizens aged 18 to 50 years.